Pengaruh Orientasi Kewirausahaan, Orientasi Pasar dan Orientasi Teknologi Terhadap Keunggulan Bersaing - Syafa'ad, Nifsa Hanipah; L V, Yuhendri (Universitas Negeri Padang, 2024)
This research aims to reveal the impact of entrepreneurial orientation, market orientation and technological orientation on competitive advantage at bordir and sulaman businesses in Bukittinggi city,. 80 people became the research sample with the total sampling technique derived from the population of bordir and sulaman business actors in Bukittinggi city. A quantitative approach with an associative type was used in the study. In addition, logistic regression was also determined as a data analysis technique in testing the research variables. The results indicate : 1) Independent variables simultaneously have a significant influence on the dependent variable. 2) Entrepreneurial orientation (X1) and Market orientation (X2) is able to significantly influence competitive advantage. 3) Technology orientation (X3) is not able to significantly affect competitive advantage.